Public Administration in the Conditions of War: Challenges and Prospects - Kryvoruchko, Iryna (Theory and Practice of Public Administration, 2023)
The article analyzes modern approaches to the concept of public administration, outlines a number of features of this concept, and defines modern challenges and key problems of public administration in the conditions of war in Ukraine.It has been established that the process of formation of the domestic system of public administration should begin with the creation of an appropriate institutional environment aimed at the formation of new value orientations for the entire society and each person separately. Particular attention is paid to guaranteeing the social well-being of society, solving urgent problems of a social and economic nature, ensuring and improving the quality of life of the population, especially in conditions of war.It is substantiated that the policy of public administration should include the implementation of the following stages: monitoring and analysis of the effectiveness of the functioning of the economy in the conditions of modern globalization processes and uncertainty under conditions of war; development and justification of the goal and key tasks of the socio-economic development of the state; the formation of an effective and efficient mechanism of the public administration system.In order to build an effective system of public administration for Ukraine, it is proposed to solve the following tasks: redistribution of powers between public authorities, as well as elimination of duplicate functions between them; expansion of opportunities for the participation of representatives of civil society in the process of public administration; increasing the level of motivation of civil servants; improving the quality of administrative services; further digitization of the public administration system; coordination of the activities of economic entities with the aim of ensuring comprehensive socio-economic development of both individual territories and the country as a whole.